Formation of odorous and hazardous by-products from the chlorination of amino acids - How, Z.; Linge, Kathryn; Busetti, F.; Joll, Cynthia (IWA Publishing, 2018)
The formation of odorous aldehydes and N-chloraldimines, and also nitriles, which are potentially hazardous to human health, was investigated in studies of the chlorination of amino acids (AAs) in both operational drinking water treatment plants and laboratory-based experiments. In the drinking water treatment plants studied, the concentration of total free AAs did not significantly change after treatment, even though good removal of DOC was observed. However, free AAs still contributed less than 3% of total nitrogen in the treated drinking waters, and no aldehydes, N-chloraldimines or nitriles of interest were detected in the treated waters, presumably due to the low concentrations of the precursor AAs in these water samples. Laboratory formation potential experiments showed that carboxylic acids can form from the degradation of aldehydes and nitriles. Volatile carboxylic acids could result in odour issues and some carboxylic acids may be of potential health concern. Therefore, carboxylic acids should also be considered as potential by-products of interest in distribution systems with long contact times of = 7days. A higher proportion of nitrile formation, and promotion of carboxylic acid formation, was observed when the chlorine to AA ratio was greater than 4 compared to when this ratio was 2.8, indicating that the Cl:AA ratio is an important factor in DBP formation pathways. This suggests that results from laboratory formation studies undertaken at these low Cl:AA ratios cannot be directly applied to ‘real’ water systems, which typically have Cl:AA ratios that are orders of magnitude higher than 4. Laboratory formation potential experiments also showed that the short-term rate of formation of aldehydes and N-chloraldimines was reduced in the presence of ammonia, although formation over longer timescales (e.g. 7 days) was not significantly different between chlorination and chloramination experiments. Therefore, the use of chloramination instead of chlorination does not appear to reduce the formation of these by-products from AAs.